Effect of 10% sodium ascorbate applied for different time periods on shear bond strength of composite to bleached enamel. - Sina Niknejad; Keyvan Saati; Parvin Khadem; Sara Valizadeh (Universidad de Concepción., 2019)
Aims: Residual peroxide on the enamel surface and in the interprismatic spaces decreases the shear bond strength (SBS) of composite to bleached enamel. Evidence shows that 10% sodium ascorbate can efficiently neutralize the singlet oxygen generated by the bleaching agents. This study aimed to assess the effect of duration of application of sodium ascorbate on SBS of composite to bleached enamel. Materials and Methods: This in vitro experimental study was conducted on 30 sound human third molars, which were randomly divided into three groups (n=10). In group 1, the teeth were bleached for 45 minutes and were then subjected to immediate bonding and restoration with composite resin. In groups 2 and 3, the teeth were bleached, immersed in 10% sodium ascorbate solution for 5 (group 2) and 10 (group 3) minutes and were then bonded and restored with composite, and the SBS was then measured. Results: The highest SBS (14.02±8.6MPa) was noted in group 3 (immersion in 10% sodium ascorbate for 10 minutes before bonding). The lowest SBS was noted in group 1 (immediate bonding after bleaching) (p<0.05). The difference in SBS of groups 1 and 2 was not significant (p=0.4). Conclusion: Application of 10% sodium ascorbate for 10 minutes increases the SBS of composite to bleached enamel.